Novel Synthesis of Sensitive Cu-ZnO Nanorod–Based Sensor for Hydrogen Peroxide Sensing - Arsalan, Muhammad; Saddique, Imram; Baoji, Miao; Awais, Azka; Khan, Ilyas; Shamseldin, Mohamed A.; Mehrez, Sadok (Frontiers in Chemistry, 2022)
In order to synthesize sensitive electrochemical sensors for hydrogen peroxide sensing by using zinc oxide nanorods grown on Fluorine-doped tin oxide electrode by facial hydrothermal method. It was important to keeping the surface morphology of material (nanorods structure), due to its large surface area and detection ability. The work presents here a non-enzymatic H2O2 sensor using vertically grown zinc oxide nanorods on electrode (FTO) surfaces deposited with Cu nano-particles. Scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Energy Dispersive X-Ray (EDX), X-ray diffraction (XRD), and electrochemical methods were used to characterized copper zinc oxide nanorods. In addition to high surface area, the hexagonal Cu-ZnO nanorods exhibited enhanced electrochemical features of H2O2 oxidation. Nanorods made from Cu-ZnO exhibit highly efficient sensitivity of 3415 μAmM−1cm−2 low detection limits (LODs) of 0.16 μM and extremely wide linear ranges (up to 11 mM). Additionally, copper zinc oxide nanorods demonstrated decent reproducibility, repeatability, stability, and selectivity after being used for H2O2 sensing in water samples. Cu nanoparticles decorated on ZnO nanorods demonstrate excellent potentials for hydrogen peroxide detection, providing a new way for preparation of hydrogen peroxide detecting devices.